2000
DOI: 10.1016/s0550-3213(99)00532-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of large-N super Yang–Mills theory AdS/CFT correspondence

Abstract: Thermodynamics of d = 4, N = 4 supersymmetric SU(N) Yang-Mills theory is studied with particular attention on perturbative expansion at weak 't Hooft coupling regime and interpolation to strong coupling regime thereof. Non-ideal gas effect to free-energy is calculated and found that leading-and next-to-leading-order corrections contribute with relative opposite signs. Padé approximant method is adopted to improve fixed-order, perturbative series and is found to decrease free-energy monotonically as 't Hooft co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…In the near-horizon limit (3.1a) with ℓ = l s → 0 we have the same term (6.22) in terms of the rescaled quantities, but with γ rescaled to γ = 1 8 ζ(3) (6.24) ‡21 On the weak coupling side, a two loop calculation [62] has shown that the leading correction in λ is negative, giving further evidence for the interpolation conjecture. In [63] further corrections in λ from the weak coupling side are considered and also found to support the interpolation conjecture.…”
Section: Corrections From Higher Derivative Termsmentioning
confidence: 66%
“…In the near-horizon limit (3.1a) with ℓ = l s → 0 we have the same term (6.22) in terms of the rescaled quantities, but with γ rescaled to γ = 1 8 ζ(3) (6.24) ‡21 On the weak coupling side, a two loop calculation [62] has shown that the leading correction in λ is negative, giving further evidence for the interpolation conjecture. In [63] further corrections in λ from the weak coupling side are considered and also found to support the interpolation conjecture.…”
Section: Corrections From Higher Derivative Termsmentioning
confidence: 66%
“…It is generally assumed (see, e.g., [52]) that f (λ) is analytic on the positive real line (i.e., that one encounters no phase transitions in extrapolating the N = 4 SYM coupling from zero to infinity; more about this in §7). In summary, the thermodynamics of the N = 4 SYM theory in flat space is qualitatively rather boring.…”
Section: Deconfinement Transitions In Gauge Theoriesmentioning
confidence: 99%
“…Recall that Phase I is a confined phase, characterized by a uniform distribution of eigenvalues for the holonomy matrix U . 52 On the other hand Phases II and III are both deconfined phases, which are distinguished by the fact that in Phase II the eigenvalue distribution is non-vanishing on the whole unit circle, while it vanishes outside an interval in Phase III. 53 Note that in each of the figures 8-11 all phase transition temperatures at strong coupling are of O(Λ QCD ); consequently, in this regime the dimensionless phase transition temperature T R increases linearly with the coupling parameter RΛ QCD .…”
Section: Possible Phase Diagrams For Large N Yang-mills Theoriesmentioning
confidence: 99%
“…The presence of the auxiliary fields affects the computation of the quadratic sector 4 in a minor way, as we will see below. Let us 3 Works that employed the Feynman diagrammatic techniques of computing the free energy at finite temperature can be found, e.g., in [16][17][18]. 4 Since the quadratic part was obtained only by using the N = 1 susy transformation rules, we expect that it would take the same form in the complete off-shell N = 4 formulation.…”
Section: Localizationmentioning
confidence: 99%